Funkcjonowanie nazw dawnych zwyczajów gospodarskich we współczesnym języku mieszkańców Kawczyna (gm. Drawsko, pow. czarnkowsko-trzcianecki) – pierzak, dożynki, szczeblik - Krępuła, Natalia (Slavia Occidentalis, 2023)
The article analyzes changes over time (temporal variation) in the name of three old farming habits: pierzak, dożynki and szczeblik. The author analyzed the materials obtained today in terms of generational diversity and compared them with archival data – Adam Tomaszewski and Atlas of the language and folk culture of Greater Poland. The analyzes showed that the generational differentiation is insignificant among the surveyed informants, while the chronological changes of the surveyed names show a varying degree of transformation.